AZAS-AZAS DAN LANDASAN DISTRIBUSI PENDAPATAN DALAM ISLAM - Rani Mulyani; Iwan Setiawan (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2019)
Abstract: This paper explains the concept of income distribution in an effort to equalize the economy. Justice and community welfare can be seen from how much the community's needs are met equally and fairly in both Primary and secondary needs. The main purpose of Islamic economic development is not only to focus on the income of individuals or groups, but also for the welfare of society in general. There are two mechanisms in the economic distribution of the community. The first mechanism is that relating to economic activities can be carried out in the productive economy sector through community development in creating jobs, providing opportunities for the community in the development of assets in the form of investment, such as syirkah, mudharabah and other investment activities. The second mechanism is Non-Economic, which is where this mechanism aims to educate people who have sufficient material so that the ownership of these assets can be educated on the importance of giving or distributing assets to disadvantaged people in the form of giving (Zakat, Infaq, Sadaqoh and also Grants). Abstrak: Tulisan ini menjelaskan mengenai Konsep Distribusi Pendapatan dalam upaya pemerataan Ekonomi. Keadilan dan kesejahteraan masyarakat dapat dilihat dari seberapa banyak terpenuhinya kebutuhan masyarakat secara merata dan adil baik dalam kebutuhan Primer dan sekunder. Tujuan pembangunan ekonomi dalam Islam tidak hanya fokus terhadap pendapatan perorangan atau suatu kelompok saja, akan tetapi untuk kesejahteraan masyarakat secara umum. Upaya pemerataan ekonomi masyarakat terdapat dua mekanisme. Mekanisme Pertama adalah yang berkaitan dengan kegiatan ekonomi dapat dilakukan dalam sektor ekonomi produktif melalui pengembangan masyarakat dalam menciptakan lapangan kerja, memberikan kesempatan kepada masyarakat dalam sektor pengembangan harta berupa investasi, seperti syirkah, mudharabah dan kegiatan investasi lainnya. Mekanisme kedua adalah Non-Ekonomi yaitu dimana mekanisme ini bertujuan untuk mengedukasi masyarakat yang memiliki kecukupan materi agar dalam kepemilikan harta tersebut dapat teredukasi pentingnya memberikan atau mendistribusikan harta yang dimiliki kepada masyarakat yang kurang beruntung berupa pemeberian (Zakat, Infak, Shadaqoh dan juga Hibah).